Guía para procedimientos de trámite de permisos en proyectos infraestructura hospitalaria para la CCSS - García-Rodríguez, José Daniel (Instituto Tecnológico de Costa Rica, 2012)
The construction of hospital infrastructures represents a great challenge from the planning stage, execution, pursuit, control and closes, since interdisciplinary equipment like doctors, architects, engineers and other people that will operate in the hospital. This work is oriented to the process of procedures for hospitable projects, which require to be programmed in such a way that the project is not delayed. It is meant to improve this process by means of a tool that let us get the necessary information; so that, the administrator makes decisions, evaluate important landmarks, and has a better control of the project. Taking as a base the construction of the new hospital of Heredia, the investigation was done with people in charge of the CCSS. Once knowing the procedures we did and the way of doing it, we visited each institution. In which I asked for the procedure and the requirements of each step, then it was processed and organized by priorities. It was obtained; as a result, the organization, planning and programming of the different proceedings done before each institution and the elaboration of a manual that describes the most important steps to take into account for the construction of a hospital.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2012.
Keywords: Planificación; Control; Programación; Requisitos; Seguimiento